491 Developing educational materials about immunotherapy for patients and their caregivers. (9th November 2020) - Gonzalo, Maria; Saxton, Claire; Fearnley, Kirstin; Karubian, Jenny; Power, Nick; Jaisle, Alyssa
Abstract : Background: As the use of immunotherapy as treatment for cancer patients continues to expand, it is important that patients and caregivers have access to relevant educational and community resources to support them in making informed decisions and receiving optimal care. To help meet these needs, the Cancer Support Community (CSC) designed Frankly Speaking About Cancer (FSAC): Immunotherapy. The intent of FSAC: Immunotherapy is to act as a patient education resource that offers information about immunotherapy, side effects, psychosocial impacts, and patient-provider communication. It is critical to gather stakeholder feedback when developing such programs to ensure all information and resources are appropriate and useful to the target audience. To achieve this, CSC worked with patients and caregivers to get feedback and refine the FSAC: Immunotherapy educational materials. Methods: In June 2020, CSC facilitated a virtual discussion board with cancer patients that have received immunotherapy (N = 8) and their caregivers (N = 2). Participants were asked to talk through and provide feedback on two booklets: FSAC: Immunotherapy and FSAC: Immunotherapy & Lung Cancer. Participants reviewed the booklets and answered open-ended questions about clarity and completeness of information. Sample points of discussion focused on their comprehension and perception of information regarding immunotherapy, immunotherapy options, side effects, and decision-making. Results: Qualitative analysis of discussion board responses revealed that while participants judged most of the content to be clear and informative, they desired more information about differences between immunotherapy types, technical terms, and cost. Specific requests included: Explain how types of immunotherapies differ from one another.Provide information on oncolytic vaccines and how they work.Clarify if immunotherapy can be used in adjuvant treatment or just in metastatic disease.Add information about costs associated with immunotherapy treatment and common practices in health insurance reimbursement. Add information about how is immunotherapy administered. Conclusions: Patients and caregivers provide valuable perspectives to those creating educational resources. Incorporating these stakeholder voices can increase the effectiveness of materials and should continue throughout the resource development processes. Regarding implementation, CSC distributes the booklets at no charge to cancer patients and caregivers via its internal network of almost 50 Cancer Support Communities and Gilda's Clubs worldwide, the CancerSupportCommunity.org webpage, and partner patient advocacy groups. We also promote these materials to the medical community and allow them to order/download it, at no charge, to help patients undergoing immunotherapy treatment and their caregivers. Acknowledgements: This project was supported by grants from Bristol Myers Squibb, Lilly, EMD Serono, and Pfizer. Ethics Approval: This study was conducted under IRB-exempt protocols [category 45 CFR 46.101(b) 2]. References: McConville H, Harvey M, Callahan C, Motley L, Difilippo H, & White C. CAR T-cell therapy effects: Review of procedures and patient education [Online exclusive]. Clinical Journal of Oncology Nursing 2017:21(3);E79–E86. https://doi.org/10.1188/17.CJON.E79-E86